Evaluating situational crime prevention using a young people's survey - Painter, Kate (The British journal of criminology, 2001)
The main aim of this research is to evaluate the impact of improved street lighting on crime in a local authority housing estate in Dudley, West Midlands. It is argued that high quality evaluation designs, for example, comparing experimental and control areas and including before and after measures of crime, are needed to evaluate situational crime prevention initiatives. Previously, in a design of this kind using household victimization surveys to measure crime, we demonstrated that crime decreased after the street lighting was improved. The main aim of this paper is to investigate whether the same results are obtained in a self-report survey of young people, also given in experimental and control areas before and after the improved street lighting. It is argued that self-reported delinquency is a valid and reliable measure of offending. The self-report results corroborated the victimization survey results in showing that offending decreased in the experimental area compared to the control area. Also, the young people thought